Metarhizium anisopliae: influence of pH on enzyme activity and control of Rhipicephalus microplus ticks - Marciano, Allan Felipe; Rodrigues, Caio Junior Balduino Coutinho; Perinotto, Wendell Marcelo de Souza; Camargo, Mariana Guedes; Gôlo, Patrícia Silva; de Sá, Fillipe Araujo; Quinelato, Simone; de Freitas, Maria Clemente; Angelo, Isabele da Costa; Nogueira, Michel Ruan dos Santos; et al. (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Marciano A.F., Coutinho-Rodrigues C.J.B., Perinotto W.M.S., Camargo M.G., Gôlo P.S., Sá F.A., Quinelato S., Freitas M.C., Angelo I.C., Nogueira M.R.S. & Bittencourt V.R.E.P. [Metarhizium anisopliae: influence of pH on enzyme activity and control of Rhipicephalus microplus ticks.] Metarhizium anisopliae: influência do pH na atividade enzimática e no controle de Rhipicephalus microplus. Revista Brasileira de Medicina Veterinária, 37(Supl.1):85-90, 2015. Departamento de Parasitologia Animal, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 47, Seropédica, RJ 23897-970, Brasil. E-mail: vaniabit@ufrrj.br Rhipicephalus microplus ticks are one of the major agents causing substantial losses to livestock worldwide. In the search for alternative control strategies, both in vitro and in vivo use of the arthropodpathogenic fungus Metarhizium anisopliae has shown promising results against this ectoparasite. During host colonization, protease production by M. anisopliae is considered one important virulence factor once it is directly related to the active penetration process carried by the fungus on the full host cuticle. Nevertheless, limitations as environmental pH may modulate the proteases production and/or activity, as well as, the fungal virulence. The current study aimed evaluate the virulence and total protease activity of M. anisopliae CG 148 sensu lato (s.l.). Fungal aqueous suspensions or 5% mineral oil formulations were used in different pH ranges (5, 7, or 9). Suspensions and formulations were prepared using a pH meter and adjusted to 108 spores mL-1. In the bioassay, four groups were formed for each pH range: the aqueous fungal suspension, the oil-based fungal formulation and their respective controls (aqueous and oil-based), totaling 12 groups. Engorged females were immersed for 3 minutes and maintained under optimal conditions for evaluation of biological parameters. Total protease activity of the artificial medium (after filtration of mycelia) was assessed by azocasein hydrolysis at 72 hours of incubation in minimal medium supplemented with 1% R. microplus cuticle. Oil-based formulations did not yield significant alterations in the fungal virulence or enzyme activity. Nevertheless, the alkaline pH at aqueous suspensions reduced total protease activity and negatively influenced fungal virulence, reducing 1.5 times tick control percent. Based on these results, it is suggested that excessive alkalinity in strictly aqueous media may potentially interfere in the in vitro arthropodpathogenic fungal virulence.